Increased adult neurogenesis in mice with a permanent overexpression of the postsynaptic 5-HT1A receptor. (28th October 2016) - Noto, Bettina; Klempin, Friederike; Alenina, Natalia; Bader, Michael; Fink, Heidrun; Sander, Svenja E.
Highlights: Depression and hippocampal adult neurogenesis (HAN) are influenced by 5-HT1A Rs. Here, we studied HAN in mice with postsynaptic overexpression of 5-HT1A R (OE). Proliferation, survival and differentiation of newborn cells were increased in OE. Alterations in survival were only detected in the female subgroup of OE mice. We propose a leading role of postsynaptic 5-HT1A Rs in HAN. Abstract: Depression is among the leading causes of disability and disease burden. Recent studies point to an involvement of altered serotonin1A receptor (5-HT1A R) –mediated adult neurogenesis in depression. However, the exact underlying mechanisms remain unclear, mainly due to the complexity of the serotonergic system with its various receptors and their locations. Mice with permanent overexpression of postsynaptic 5-HT1A Rs (OE mice) represent a unique tool for investigating the involvement of postsynaptic 5-HT1A Rs in this context. Correct 5-HT1A R coupling and functioning has been demonstrated earlier, indicating that more postsynaptic 5-HT1A Rs can be activated in these mice. Initially we examined morphometric parameters of the dentate gyrus (DG) and the prefrontal cortex as they are involved in adult hippocampal neurogenesis and/or depression. The volume of the DG in OE mice was increased in comparison to wildtype controls. We therefore investigated parameters of adult neurogenesis by the bromodeoxyuridine method. Proliferation and survival of newborn cells in the DG of OE mice were significantly increased. Significant increases in survived neurons were only detected in the female but not in the male subgroup. Additional staining for early precursor cells (Sox2) and progenitor cells of the neuronal lineage (doublecortin) showed an increase in type-1/2a as well as in type-2b/3 cells in OE mice. Our study suggests a leading role of the postsynaptic 5-HT1A R in adult hippocampal neurogenesis and might open an important link to depression.